Amino Acid Differences in the 1753-to-1851 Region of TcdB Influence Variations in TcdB1 and TcdB2 Cell Entry - Jonathan J. Hunt (American Society for Microbiology, 2017)
ABSTRACT Clostridium difficile TcdB2 enters cells with a higher efficiency than TcdB1 and exhibits an overall higher level of toxicity. However, the TcdB2-specific sequences that account for more efficient cell entry have not been reported. In this study, we examined the contribution of carboxy-terminal sequence differences to TcdB activity by comparing the binding, uptake, and endosomal localization of TcdB1 and TcdB2 or selected recombinant fragments of these proteins. Our findings suggest that sequence differences in the amino acid 1753 to 1851 region proximal to the combined repetitive oligopeptide domain (CROP) support enhanced uptake of TcdB2 and localization of toxin in acidified endosomes. In the absence of this region, the CROP domains of both forms of the toxin exhibited similar levels of cell interaction, while the addition of amino acids 1753 to 1851 greatly increased toxin binding by only TcdB2. Moreover, the amino acid 1753 to 2366 fragment of TcdB2, but not TcdB1, accumulated to detectable levels in acidified endosomes. Unexpectedly, we discovered an unusual relationship between endocytosis and the efficiency of cell binding for TcdB1 and TcdB2 wherein inhibition of endocytosis by a chemical inhibitor or incubation at a low temperature resulted in a dramatic reduction in cell binding. These findings provide information on sequence variations that may contribute to differences in TcdB1 and TcdB2 toxicity and reveal a heretofore unknown connection between endocytosis and cell binding for this toxin. IMPORTANCE TcdB is a major virulence factor produced by Clostridium difficile, a leading cause of antibiotic-associated diarrhea. Hypervirulent strains of C. difficile encode a variant of TcdB (TcdB2) that is more toxic than toxin derived from historical strains (TcdB1). Though TcdB1 and TcdB2 exhibit 92% overall identity, a 99-amino-acid region previously associated with cell entry and spanning amino acids 1753 to 1851 has only 77% sequence identity. Results from the present study indicate that the substantial sequence variation in this region could contribute to the differences in cell entry between TcdB1 and TcdB2 and possibly explain TcdB2’s heightened toxicity. Finally, during the course of these studies, an unusual aspect of TcdB cell entry was discovered wherein cell binding appeared to depend on endocytosis. These findings provide insight into TcdB’s variant forms and their mechanisms of cell entry.